Pengaruh Komsumsi Tempe Kukus Terhadap Hot Flushes Pada Ibu Hamil Trimester III - Prianti, Ani T.; Rustam, Harmawati; Mirna, Mirna; Ohorella, Fadjriah (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Pregnancy is a period during which the body's immune function declines due to hormonal changes when pregnant, especially in cases of overweight or obesity, which also increases the risk of experiencing hot flashes. Hot flashes are normal symptoms but still require immediate management. Tempeh is a traditional Indonesian food made from soybeans that is rich in isoflavones. The aim of this research is to determine the effect of steamed tempeh consumption on the management of hot flashes in pregnant women in their third trimester at the Antang Public Health Center in 2024. The type of research used is quantitative research with a pre-experimental design, one group pre-test – post-test. The number of respondents in this study is 36 respondents. The technique used is purposive sampling. The statistical test results using the Wilcoxon signed-rank test show a p value of (0.000), which is less than 0.05 (p < α). The consumption of steamed tempeh affects the management of hot flushes in pregnant women in the third trimester in the working area of the Antang Health Center.